Workload, Workplace Spirituality, Organizational Commitment and Turnover Intention in Nurses at M Hospital of Banten, Indonesia - Tobias Reinaldo Toti; Endang Ruswanti; Rokiah Kusumapradja (Penerbit Kemala Indonesia, 2020)
Turnover nurses it’s one of the main problems in hospitals. Outgoing nurses with significant costs to recruiting a new employee, orientation fees, and training new employees it was very harmful for hospital. Thus, this study aimed to determine the effect of workload and workplace spirituality on turnover intention with organizational commitment as an intervening variable in nurses at M hospital. In this study, we collect the data observation from questionnaires at M hospital with 124 nurse respondents using the convenience sampling method. The explanatory causal research model with Path Analysis was used in this study. The results showed that a Workload, Workplace Spirituality, and Organizational Commitment simultaneously influence Turnover Intention, Workload influences Organizational Commitment, Workplace Spirituality influences Organizational Commitment, Organizational Commitment does not influence Turnover Intention, Workload influences Turnover Intention and Workplace Spirituality does not influence Turnover Intention. The research implication is that to reduce the nurse turnover intention, it is necessary to make a workload analysis, arrange the assignment system and make an amount of staff to reduce the workload of nurses in M hospital.